If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 + -5x = 28 + -2x Solving 42 + -5x = 28 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 42 + -5x + 2x = 28 + -2x + 2x Combine like terms: -5x + 2x = -3x 42 + -3x = 28 + -2x + 2x Combine like terms: -2x + 2x = 0 42 + -3x = 28 + 0 42 + -3x = 28 Add '-42' to each side of the equation. 42 + -42 + -3x = 28 + -42 Combine like terms: 42 + -42 = 0 0 + -3x = 28 + -42 -3x = 28 + -42 Combine like terms: 28 + -42 = -14 -3x = -14 Divide each side by '-3'. x = 4.666666667 Simplifying x = 4.666666667
| 15x^2-6x=153 | | 4k-3=7 | | 30+64=4x-6 | | 1.5X-6=50 | | 2-z=-2 | | 31/2x(1-3)^4 | | 8y-2y=60 | | 3x+7=28-2x | | 6(y-1)=2y+8 | | 4/53/8 | | 5x=12x-6x | | 0.25x+0.1y=1.8 | | 1/31/4 | | 9x-6l=-16 | | 0.8-4(b-1)=0.2+3(4-3) | | -4.9x^2+90x=0 | | (a+1)=9 | | 5/8/2/4 | | 5X+5H+1-(5X+1)= | | 2x^2+2xy-3y^2=2 | | 2x+95=6x+43 | | 3.5Y+5=13.5Y+14 | | 7x-2=8x+17 | | x^4-6x^3+12x^2-4x-1=0 | | 65=v/5 | | 3(x+6)=6(x-3)+x | | 0=2sin(4x-3)-3 | | 14(2t+10)=-80 | | 2x^2-24=8x | | -10(s+1)=65 | | 9-2x=3x | | 1/x-1/r=1/s-!/x |